Pengaruh Struktur Modal dan Ukuran Perusahaan Terhadap Nilai Perusahaan pada Perusahaan Sektor Keuangan yang Terdaftar di Bursa Efek Indonesia - Suparyono Suparyono; Endang Kartini Panggiarti (Jurnal Akuntan Publik, 2023)
This study aims to determine the effect of capital structure and company size on the value of financial sector companies. The data used is secondary data in the form of company financial reports listed on the Indonesia Stock Exchange. The samples used in this study were 47 financial sector companies listed on the Indonesia Stock Exchange. The data processing technique uses multiple linear regression which is carried out using the SPSS application. The results of the research that has been done are that there is no significant effect of capital structure and company size on the value of financial sector firms either simultaneously or partially.